Effects of an intervention on the participation of people with disability in the workplace - VILELA,Laiza Oliveira (2017)
Abstract Current laws and regulations have generated discussions about the accessibility of disabled people in the labor force. However, there is a need for changes in the physical, functional, and attitudinal and/or behavioral environment to create an inclusive environment. The objective of this research was to evaluate the effects of an intervention aimed at a critical reflection on the inclusion of people with disabilities in the workplace. The intervention was carried out in a higher education institution with academic staff and administrators; its effects were evaluated using the Conceptions of Disability Inventory. The results indicated that after having completed the course, the participants developed a broader and more human conception of the participation of people with disabilities in the workplace.